Isomalabaricane Triterpenes from the Marine Sponge Rhabdastrella sp. - Kuei-Hung Lai; Zheng-Hao Huang; Mohamed El-Shazly; Bo-Rong Peng; Wen-Chi Wei; Jui-Hsin Su (Marine Drugs, 2021)
The marine sponge of the genus Geodia, Jaspis, Rhabdastrella, and Stelletta are characterized chemically by a variety of isomalabaricane triterpenes. This class of compounds drew spotlights in marine lead discovery due to their profound anti-proliferative properties. Further research on exploring its chemical diversity led to the identifications of two new isomalabaricane-type triterpenes rhabdastin H (1) and rhabdastin I (2). Their structures were unraveled using a series of spectroscopic approaches. These isolates were found to exhibit unique structural features with the only reported tetrahydrofuran functionality among all marine-derived isomalabaricanes. Both compounds 1 and 2 showed activities against K562 (IC50 11.7 and 9.8 μM) and Molt4 (IC50 16.5 and 11.0 μM) leukemic cells in MTT cell proliferative assay.